2017 IEEE Photonics Conference (IPC) 2017
DOI: 10.1109/ipcon.2017.8116236
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of light trapping micro-hole structure for high-speed high-efficiency silicon photodiodes

Abstract: We optimized micro-holes in a thin slab for fast Si photodetectors at wavelength 800-950nm. Lateral modes are shown to be responsible for the effective light trapping. Small disorder and cone hole shapes helped achieve uniform quantum efficiency in a wide wavelength range. SummeryThe Si pin PDs at the short-reach multimode datacom wavelengths of 840-860 nm and at a short wavelength division multiplexing (SWDM) band of 850-950 nm could facilitate the integration [1] and reduce the cost. Our recent study [2] sho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Two basic geometries were studied: Si thickness t=1000nm with the inverted pyramids arranged in square lattice between electrodes with period p=500nm and side a=500nm; and the thickness t=2000nm, p=1000nm, a=700nm. As it was shown in [2][3][4] the holes array supports a set of modes with wave vectors in z direction, kz and kc in x-y plane. Each hole couples the vertically incident light into the x-y plane.…”
Section: Design and Simulationsmentioning
confidence: 80%
See 1 more Smart Citation
“…Two basic geometries were studied: Si thickness t=1000nm with the inverted pyramids arranged in square lattice between electrodes with period p=500nm and side a=500nm; and the thickness t=2000nm, p=1000nm, a=700nm. As it was shown in [2][3][4] the holes array supports a set of modes with wave vectors in z direction, kz and kc in x-y plane. Each hole couples the vertically incident light into the x-y plane.…”
Section: Design and Simulationsmentioning
confidence: 80%
“…The Si MSM photodetectors (PDs) at the short-reach multimode datacom wavelengths of 840-860 nm and at a short wavelength division multiplexing (SWDM) band of 850-950 nm could facilitate the integration [1] and reduce the cost. Our study [2,3] showed theoretically and experimentally that a nano-or micro-structure can increase the Si PDs quantum efficiency (QE) for pin diodes so that less than 2 microns intrinsic (i) layer can show the QE>50% with data rate 20 Gb/s for wavelength 800-950nm. In this study we use nanoholes to reduce the reflection and increase QE in MSM PDs.…”
Section: Introductionmentioning
confidence: 90%
“…The field distribution around the cylindrical holes (Fig.1e) shows the lateral modes between the holes. The tapered or inverter pyramids shape had smaller reflection due to the effect is similar to the Lambertian reflector that helps to trap infrared radiation [5]. The micro-holes also provide better absorption in wider region.…”
mentioning
confidence: 96%
“…The lateral modes with larger kc can have full reflection from the bottom of the PD and they can form modes guided in the x-y plane in b-AsP layer. The lateral modes [4,5] in xy plane causing higher absorption. The FDTD simulation for the inverted pyramids holes in SiO2 cover with period 2000nm and diameter of 1700nm ( Fig.1d green curve) shows some absorption increase over flat cover (Fig.1d, black curve).…”
mentioning
confidence: 99%
See 1 more Smart Citation